Effect of leukocyte and platelet-rich plasma on osseointegration after implant placement in mouse maxilla - Mauricio Zapata-Sifuentes; Angela Quispe-Salcedo; Taisuke Watanabe; Tomoyuki Kawase; Hayato Ohshima (Regenerative Therapy)
Introduction: Osseointegration, the direct contact between an implant and bone, can be achieved by direct and/or indirect osteogenesis. Platelet-rich plasma accelerates tissue regeneration, wound healing, and osseointegration. This study aimed to analyze the effects of leukocyte and platelet-rich plasma (L-PRP) on direct and indirect osteogenesis after implant placement in a mouse maxilla. Methods: Blood was collected from the tail vein of 4–8-week-old male ICR mice and L-PRP was obtained after double-spin cycle centrifugation. After the right upper first molars of 4-week-old ICR mice were extracted while under deep anesthesia, the alveolar sockets were prepared with a drill, and titanium implants blasted with hydroxyapatite/β-tricalcium phosphate were placed into the cavity filled with 1.5 μL of L-PRP. Samples were collected from the animals 3–28 days after implantation, and immunohistochemistry for osteopontin, Ki67 (cell proliferation marker), cathepsin-K (osteoclast marker), and osteonectin (osteoblast marker) was performed. Results: Cell proliferation was significantly higher in the L-PRP group than in the control group on postoperative days 3 and 5. The activities of osteoclast-lineage cells and osteoblasts increased significantly on day 5 in the L-PRP group, indicating that L-PRP evoked an active cellular response. Indirect osteogenesis was significantly higher on days 7, 14, and 28, and the osseointegration rate was significantly higher on day 28 in the L-PRP group compared with the control group. Conclusions: L-PRP enhances osseointegration by promoting mesenchymal cell proliferation, osteoclastic and osteoblastic activities, and indirect osteogenesis.